Puntuación de pancreatitis aguda inofensiva positiva y evolución intrahospitalaria no severa de pacientes con pancreatitis aguda - Saavedra Díaz, Susan Paola (2017)
Several predictors of severity have been studied for Acute Pancreatitis (PA). Recently, a new score, "Harmless Acute Pancreatitis Score" (PPAI), which could be an ideal predictor of the severity of the evolution of this pathology, has been studied. Objetive: this study will establish the association between positive PPAI and intrahospital non severe evolution in PA. Materials and methods: the study was a prospective cohort, wich include patients admitted to the Hospital Belén de Trujillo and Hospital Regional Docente de Trujillo between the months January-August 2016. These patients were evaluated during the first 60 minutes of admission, according PPAI’s criteria. Positive PPAI was classified as positive if there were no signs of peritonitis (rebound sign and / or abdominal tension on palpation), hematocrit <43% in men and <39.6% in women, and creatinine <2 mg / dL; the absence of one of them was considered PPAI negative. On the third day of follow-up, they were sub-classified into intrahospital severe or non-severe evolution according to APACHE II. Results: 219 patients with PA were admitted, of whom 60 were excluded. 32 patients were PPAI positive, of which 31 had a intrahospital non-severe evolution, and 64 were PPAI negative, evolving non-severe 50 patients. RR = 1.24, with a confidence interval of 1.08 <RR <1.43 (X2 = 5.69, p <0.05). Conclusion: PPAI positive is associated with a intrahospital non-severe evolution of PA